Possible links between groundwater geochemistry and chronic kidney disease of unknown etiology (CKDu): an investigation from the Ginnoruwa Region in Sri Lanka - Balasooriya, S.; Munasinghe, H.; Herath, A. T.; Diyabalanage, S.; Ileperuma, O. A. (Springer, 2020)
Since at least two decades, Chronic Kidney Disease of Uncertain Etiology (CKDu) has become an increasingly discussed health issue in Sri Lanka and as well as in other tropical regions. Areas that are particularly afected with the disease are mostly located in the dry zone of Sri Lanka. The disease is more prominent among communities that consume groundwater as their main source of drinking water. Hydrogeochemical investigations were carried out in the Ginnoruwa area, a known hotspot of CKDu. It revealed possible links between drinking water chemistry and the spreading of the disease. This work compares hydrogeochemical data of drinking water sources of wells whose consumers are afected by CKDu and other nearby wells whose consumers were not afected by the disease. A total of 63 groundwater samples were collected from selected wells. About one-third of these samples (i.e., 19) were collected from wells used by CKDu patients. Signifcantly higher values of pH, total hardness, electrical conductivity, Ca2+, Mg2+, F-, Cl-, PO4 3-, and SO4 2- were found in wells that were used by CKDu patients. Mean contents of Na+, Ca2+, and Mg2+ in CKDu afected wells were 33.8 mg/L, 30.1 mg/L, and 14.9 mg/L, respectively, compared to 23.1 mg/L, 26.7 mg/L, and 9.65 mg/L in non-CKDu wells. Diferences in major ion geochemistry in groundwaters are possibly governed by variable time periods of water storage in fractured hard rock aquifers in this region. Hydrogeochemical parameters were statistically compared by a Mann–Whitney U test and indicated signifcant diferences in total dissolved solids (TDS) (p=0.016), SO4 2- (p=0.005), PO4 3- (p=0.030), F- (p=0.048), Na+ (p=0.008), and Mg2+(p=0.008) between non-CKDu and CKDu wells at p=0.050 level. Other suspected solutes such as nephrotoxic trace elements including As, Cd, and Pb were similar in both types of wells. They were also lower than the accepted guideline limits of the World Health Organization (WHO). Results of this study suggest that fuoride in drinking water in combination with water hardness may be one of the responsible factors for kidney damage and progression of the disease. This may be particularly the case when elevated amounts of Mg2+ are present in hard groundwater.